Reactions to the use of evidence-based performance indicators in primary care: a qualitative study. Issue 3 (1st September 2000) - Wilkinson, Emma K; McColl, Alastair; Exworthy, Mark; Roderick, Paul; Smith, Helen; Moore, Michael; Gabbay, John
Abstract : Objectives —To investigate reactions to the use of evidence-based cardiovascular and stroke performance indicators within one primary care group. Design —Qualitative analysis of semi-structured interviews. Setting —Fifteen practices from a primary care group in southern England. Participants —Fifty two primary health care professionals including 29 general practitioners, 11 practice managers, and 12 practice nurses. Main outcome measures —Participants' perceptions towards and actions made in response to these indicators. The barriers and facilitators in using these indicators to change practice. Results —Barriers to the use of the indicators were their data quality and their technical specifications, including definitions of diseases such as heart failure and the threshold for interventions such as blood pressure control. Nevertheless, the indicators were sufficiently credible to prompt most of those in primary care teams to reflect on some aspect of their performance. The most common response was to improve data quality through increased or improved accuracy of recording. There was a lack of a coordinated team approach to decision making. Primary care teams placed little importance on the potential for performance indicators to identify and address inequalities in services between practices. The most common barrier to change was a lack of time and resources to act upon indicators. Conclusion —For the effective implementation of national performance indicators there are many barriers to overcome at individual, practice, and primary care group levels. Additional training and resources are required for improvements in data quality and collection, further education of all members of primary care teams, and measures to foster organisational development within practices. Unless these barriers are addressed, performance indicators could initially increase apparent variation between practices.